Japanese guidelines for the management of pemphigoid (including epidermolysis bullosa acquisita). Issue 12 (24th October 2019) - Ujiie, Hideyuki; Iwata, Hiroaki; Yamagami, Jun; Nakama, Takekuni; Aoyama, Yumi; Ikeda, Shigaku; Ishii, Norito; Iwatsuki, Keiji; Kurosawa, Michiko; Sawamura, Daisuke; Tanikawa, Akiko; Tsuruta, Daisuke; et al.
Abstract: The pemphigoid group is a category of autoimmune subepidermal blistering diseases in which autoantibodies deposit linearly at the epidermal basement membrane zone (BMZ). The main subtypes of pemphigoid mediated by immunoglobulin G autoantibodies are bullous pemphigoid (BP), mucous membrane pemphigoid (MMP) and epidermolysis bullosa acquisita (EBA). To establish the first guidelines approved by the Japanese Dermatological Association for the management of pemphigoid diseases, the Committee for Guidelines for the Management of Pemphigoid Diseases (Including EBA) was founded as part of the Study Group for Rare Intractable Skin Diseases under the Ministry of Health, Labor and Welfare Research Project on Overcoming Intractable Diseases. These guidelines aim to provide current information for the management of BP, MMP and EBA in Japan. Based on evidence, the guidelines summarize the clinical and immunological manifestations, pathophysiologies, diagnostic criteria, disease severity determination criteria, treatment algorithms and treatment recommendations. Because of the rarity of these diseases, there are few clinical studies with a high degree of evidence, so several parts of these guidelines were established based on the opinions of the Committee. To further optimize these guidelines, periodic revision in line with the new evidence is necessary.